Positive organizational behavior - Peterson, Suzanne J. (Henry Stewart Talks, 2012)
Psychological capacities, Positive psychology, Positive organizational scholarship, POS, POB, Human strengths, Flourishing, Trait-state continuum, State-like constructs, Hope, Optimism, Resilience, Self-efficacy, Psychological capital, PsyCap, Developmental capacities, Human Capital, Core construct, Psychological capital questionnaire, PCQ, Performance impact, Performance improvement, Positive leadership, Psychological capital and teams, Training interventions and psychological capital
Reviewed at 2018/09/27